High-intensity interval training combining rowing and cycling efficiently improves insulin sensitivity, body composition and VO2max in men with obesity and type 2 diabetes - Petersen, Maria Houborg; de Almeida, Martin Eisemann; Wentorf, Emil Kleis; Jensen, Kurt; Ørtenblad, Niels; Højlund, Kurt (Frontiers in Endocrinology, 2022)
Aims Non-weight-bearing high-intensity interval training (HIIT) involving several muscle groups may efficiently improve metabolic health without compromising adherence in obesity and type 2 diabetes. In a non-randomized intervention study, we examined the effect of a novel HIIT-protocol, recruiting both lower and upper body muscles, on insulin sensitivity, measures of metabolic health and adherence in obesity and type 2 diabetes. Methods In 15 obese men with type 2 diabetes and age-matched obese (n=15) and lean (n=18) glucose-tolerant men, the effects of 8-weeks supervised HIIT combining rowing and cycling on ergometers (3 sessions/week) were examined by DXA-scan, incremental exercise test and hyperinsulinemic-euglycemic clamp combined with indirect calorimetry. Results At baseline, insulin-stimulated glucose disposal rate (GDR) was ~40% reduced in the diabetic vs the non-diabetic groups (all p<0.01). In response to HIIT, insulin-stimulated GDR increased ~30-40% in all groups (all p<0.01) entirely explained by increased glucose storage. These changes were accompanied by ~8-15% increases in VO2max, (all p<0.01), decreased total fat mass and increased lean body mass in all groups (all p<0.05). There were no correlations between these training adaptations and no group-differences in these responses. HbA1c showed a clinically relevant decrease in men with type 2 diabetes (4+/-2 mmol/mol; p<0.05). Importantly, adherence was high (>95%) in all groups and no injuries were reported. Conclusions A novel HIIT-protocol recruiting lower and upper body muscles efficiently improves insulin sensitivity, VO2max and body composition with intact responses in obesity and type 2 diabetes. The high adherence and lack of injuries show that non-weight-bearing HIIT involving several muscle groups is a promising mode of exercise training in obesity and type 2 diabetes.